2020
DOI: 10.1002/jmv.26371
|View full text |Cite
|
Sign up to set email alerts
|

The impact of socioeconomic status on 30‐day mortality in hospitalized patients with COVID‐19 infection

Abstract: Socioeconomic status (SES) impacts outcome in a number of diseases. Our aim was to compare the outcome of hospitalized coronavirus disease 219 (COVID-19) patients in low and high SES group. Prospective cohort study of hospitalized patients with confirmed COVID-19 in three acute hospitals. Electronic case notes were analyzed for baseline characteristics and admission investigations. Scottish index for multiple deprivation (SIMD) was used to divide patients into two groups: more deprived (SIMD 1-5) and less depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 31 publications
(53 reference statements)
3
13
1
Order By: Relevance
“…These findings could reflect the known social gradient in co-morbidities and risk factors for COVID-19 severity, such as obesity, diabetes, cardiovascular disease or respiratory diseases, by which those living in the most deprived areas suffer the biggest burden. However, a study in Scotland on mortality in hospitalised patients with COVID-19 infection did not find differences in case-fatality according to deprivation in the area of residence (50). Equally, we did not find an association between the deprivation level of the municipality of residence and the risk of hospitalisation or death.…”
Section: Strengths and Weaknesses In Relation To Other Studies Discucontrasting
confidence: 89%
See 1 more Smart Citation
“…These findings could reflect the known social gradient in co-morbidities and risk factors for COVID-19 severity, such as obesity, diabetes, cardiovascular disease or respiratory diseases, by which those living in the most deprived areas suffer the biggest burden. However, a study in Scotland on mortality in hospitalised patients with COVID-19 infection did not find differences in case-fatality according to deprivation in the area of residence (50). Equally, we did not find an association between the deprivation level of the municipality of residence and the risk of hospitalisation or death.…”
Section: Strengths and Weaknesses In Relation To Other Studies Discucontrasting
confidence: 89%
“…Another possible explanation may lie in the methodological differences across studies, as there is significant heterogeneity in the indicators used to assess deprivation and the geographical areas studied. This could explain why, for example, other studies carried out in the UK and the US have not found such association (53)(54)(55).…”
Section: Strengths and Weaknesses In Relation To Other Studies Discumentioning
confidence: 93%
“…Another possible explanation may lie in the methodological differences across studies, as there is significant heterogeneity in the indicators used to assess deprivation and the geographical areas studied. This could explain why, for example, other studies carried out in the UK and the US have not found such association ( Guha et al, 2020 ; Apea et al, 2021 ; Khan et al, 2020b ). Further studies would help in clarifying the individual and contextual influence of deprivation on COVID-19 outcomes.…”
Section: Discussionmentioning
confidence: 92%
“…These findings could reflect the known social gradient in co-morbidities and risk factors for COVID-19 severity, such as obesity, diabetes, cardiovascular disease or respiratory diseases, by which those living in the most deprived areas suffer the biggest burden. However, a study in Scotland on mortality in hospitalized patients with COVID-19 infection did not find differences in case-fatality according to deprivation in the area of residence ( Khan et al, 2020a ). Equally, we did not find an association between the deprivation level of the municipality of residence and the risk of hospitalisation or death.…”
Section: Discussionmentioning
confidence: 93%
“…Despite the fact that race, ethnicity, and socioeconomic status are known risk factors for obesity, we did not observe significant differences in these social determinants of health across BMI categories. Similarly, a prospective study conducted in Scotland did not find a difference in mortality or complications in hospitalized patients with COVID-19 with higher distress scores based on the Scottish Index for Multiple Deprivation (SIMD) [ 42 , 43 ]. Although there is a disproportionate burden of COVID-19 related outcomes among Black and Latinx individuals throughout the United States [ 6 , 44 – 54 ], like ours, the plurality of retrospective cohort studies have not demonstrated significant associations between race, ethnicity, and hospital mortality.…”
Section: Discussionmentioning
confidence: 99%